Bilateral Pigment Dispersion Syndrome (PDS) in a Young Female Patient - Karunika, Anindya Ramadian; Komaratih, Evelyn; Nurwasis; Primitasari, Yulia (Universitas Airlangga, 2025)
Introduction: Pigment dispersion syndrome (PDS) is characterized by pigment accumulation in the anterior chamber and a concave peripheral iris. Many PDS patients are not diagnosed until the disease has progressed to pigmentary glaucoma or other visual problems. Since glaucoma is the primary cause of permanent blindness globally, it is crucial to perform a thorough examination on patients with PDS to identify early indicators of pigmentary glaucoma (PG). Case Presentation: A 17-year-old female presented to the ophthalmology outpatient unit with eye pain and headache. The intraocular pressure (IOP) in the right eye was 30 mmHg, while in the left eye, it was 20.5 mmHg due to the peripheral iris' concavity and heavy pigmentation in the trabecular mesh in both eyes. The patient was diagnosed with pigment dispersion syndrome in both eyes and was given timolol maleate 0.5% eye drops. A follow-up examination revealed a decrease in the IOP and pain. Conclusions: Many young PDS patients go undiagnosed, and those with glaucoma are misdiagnosed as having juvenile onset glaucoma or primary open angle glaucoma. When high IOP is seen in young myopic patients, a thorough evaluation of the anterior segment is required. The patient should be aware of the progression of PG, and regular follow-up is recommended.